A O01 Ursodeoxycholic acid for the prevention of gall stones after laparoscopic sleeve gastrectomy: a prospective controlled study. (7th December 2022) - Salman, Mohamed; Issa, Mohamed; Noureldin, Khaled; Khalid, Sadaf; Elewa, Ahmed; Shaaban, Hossam; Salman, Ahmed; Gebril, Mahmoud; Tourkey, Mohamed; Elhaj, Mujahid; Elsherbiney, Mohammed
Abstract: Background: Obesity is a risk factor for cholelithiasis. Besides, rapid weight loss after bariatric surgery upsurges the rate of cholelithiasis and acute cholecystitis. This study aimed to compare gallstone development frequency after LSG under ursodeoxycholic acid (UDCA) prophylaxis. Methods: This prospective controlled study included 332 patients scheduled for LSG randomized to receive 500 mg UDCA daily for 12 months (UDCA Group) or no treatment (Control Group). Ultrasonography was done 6 and 12 months after surgery to detect gallstones. Cholecystectomy was done for complicated cases of cholelithiasis. Results: Seventy-one patients were lost to follow-up, and 3 developed severe adverse effects of UDCA and were excluded. Data are presented for 130 patients in the UDCA group and 128 in the Control group. Collectively, 11 patients (8.5%) of the UDCA group and 41 (32.0%) of the Control group developed gall stones during the first postoperative year (p < 0.001). Cholecystectomy was indicated in 3 patients (2.3%) of the UDCA group and 9 (7.0%) of the Control group (p = 0.072). On multivariate analysis, higher BMI, dyslipidemia, and lacking UDCA prophylaxis were the independent factors significantly associated with stone development. Also, stone development was associated with higher weight loss after 6 and 12 months. Conclusions: UDCA 500 mg once daily for 12 months after LSG is effective in reducing gallstone formation at 1 year. UDCA administration reduced the frequency of cholecystectomies from 7 to 2.3%. High BMI and dyslipidemia are the independent preoperative factors significantly associated with stone development.